Implikasi Perceraian Orang Tua Terhadap Moral Anak Prespektif Teori Anomie Emile Durkheim - Kabul Wiono; Yasir Fauzi, Mohammad; Dharmayani (Kartika: Jurnal Studi Keislaman, 2026)
Parental divorce has multidimensional impacts on children's moral development, yet studies integrating Islamic Family Law and Émile Durkheim's Anomie Theory remain limited. This research aims to analyze the implications of parental divorce on children's morality from the perspective of Islamic Family Law and to explain this phenomenon through the framework of Émile Durkheim's Anomie Theory. This study employs a qualitative approach using library research method, analyzing various relevant literature ranging from legislation, statistical reports, scientific journals, to Durkheim's classical works. The findings reveal that parental divorce triggers anomie conditions manifested in three patterns of implications: normative crisis, socio-emotional isolation, and deviant behavior. Islamic Family Law, through the concepts of hadhanah and maqashid al-syari'ah, offers a comprehensive framework for protecting children's morality, yet its implementation requires a more holistic reformulation. This study recommends strengthening mandatory mediation mechanisms, family restoration programs, and integrated post-divorce supervision.